2021
DOI: 10.14639/0392-100x-n0609
|View full text |Cite
|
Sign up to set email alerts
|

Retrosigmoidal placement of an active transcutaneous bone conduction implant: surgical and audiological perspectives in a multicentre study

Abstract: SUMMARY Introduction The retrosigmoidal (RS) placement of the Bonebridge system (BB) has been advocated for cases of unfavourable anatomical or clinical conditions which contraindicate transmastoid-presigmoidal positioning. However, these disadvantageous conditions, combined with the considerable dimensions of the implant, may represent a challenge, especially for surgeons with no skull base experience. Moreover, the literature reports only limited experience concerning RS implantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In the current literature, several strategies have been explored to improve MRI image quality in the presence of the CI magnet, including the adaptation of CI angular position or distance from the external auditory canal [ 27 , 28 ], patient head orientation [ 29 ], and MRI algorithm manipulation [ 30 ]. In this respect, the application of metal artifact reduction sequences (MARS) has recently been shown to be a valuable additional strategy for improving image quality in the presence of CIs, particularly in the case of skull base disorders requiring MRI monitoring [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current literature, several strategies have been explored to improve MRI image quality in the presence of the CI magnet, including the adaptation of CI angular position or distance from the external auditory canal [ 27 , 28 ], patient head orientation [ 29 ], and MRI algorithm manipulation [ 30 ]. In this respect, the application of metal artifact reduction sequences (MARS) has recently been shown to be a valuable additional strategy for improving image quality in the presence of CIs, particularly in the case of skull base disorders requiring MRI monitoring [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Profoundly deaf patients require an effective hearing rehabilitation and when deafness is concomitant with chronic refractory middle ear pathologies, hearing rehabilitation must be combined with the successful eradication of the disease. While some bone conduction hearing implants can be positioned away from an open cavity or a chronically discharging middle ear 19 , cochlear implantation in these scenarios seems hazardous. SP overcomes these limits, resulting in a “safe and dry” cavity that is optimal for COI positioning 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Three other studies report average EGs for CMHL using the bone conduction in the implanted ear rather than the ear with the best bone conduction. These studies report EGs ranging from −16.9 to −11.0 dB (17,31,32). We found only one study that used the bone conduction of the best hearing ear and reported EGs of −8.8 and −11.3 dB for 10 subjects with mixed hearing loss and 15 subjects with SSD, respectively (18).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the CMHL group had an average total GBI of 31.7 and this is in concordance with other studies (16,36). Some studies only report combined results for SSD and CMHL groups, which makes the results difficult to interpret (31,37,38). In our study, the proportion of constant users was significantly higher in the CMHL group than in the group with SSD (Table 2).…”
Section: Discussionmentioning
confidence: 99%